Analysis of the Influence of Environmental Conditions, Communication Level and Motivation Level on the Performance of Automotive Industry Employees - Santi, Neta Mirda; Goestjahjanti, Francisca Sestri; winanti, winanti; Himmy’azz, Istajib Kulla; Kurniawati, Nia; Mendrofa, Yeremia; Karyono, Karyono; Kumoro, Dwi Ferdiyatmoko Cahya; Putriani, RDN Dwi; Solaiman, Deny (Journal of E-business and Management Science, 2024)
The importance of working environmental conditions, level of communication and level of motivation in determining the success of employee performance and until now there are still many companies that do not pay attention to these three things. There are still many companies that only seek profits without caring about the work environment, low communication and low employee motivation. Research variables: Working Environmental Conditions X1, Communication Level X2, Motivation Level The sampling technique uses Slovin samples. Data were collected using a questionnaire with a Likert scale, namely asking respondents for statements regarding the respondent's level of agreement with the questionnaire statements. Meanwhile, data analysis carried out included validity tests, reliability tests, descriptive statistical tests, normality tests, multicollinearity tests, heteroscedasticity tests, simultaneous and partial correlation tests, simultaneous and partial coefficient of determination tests, simultaneous and partial regression tests, hypothesis tests (T-tests and F-test). The research results can be seen from the multiple correlation level value of 0.898, this shows that the correlation level has a very strong influence. The coefficient of determination value is 0.806, meaning that the variables of work environment conditions, level of communication and level of motivation have an influence on employee performance of 80.6% and the remaining 19.4% is influenced by other variables not examined in this research. Meanwhile, the results of simultaneous hypothesis testing show a significant effect because Fcount > Ftable (43.924 > 3.11).